Respuesta :

Answer: Arithmetic

==================================================

Explanation:

Add -3 to each term to get the next term. This is the same as subtracting 3 from each term. In this case, the common difference is d = -3.

The first term is a = 20

---------

The nth term formula for the arithmetic sequence is

a(n) = a+d(n-1)

a(n) = 20+(-3)(n-1)

a(n) = 20-3n+3

a(n) = -3n+23

If we plug in n = 1, we would get a(n) = 20. Plug in n = 2 to get a(n) = 17. And so on. This helps confirm we have the correct nth term formula.